LSM2 drives glioma progression through alternative splicing dysregulation: a multi-omics approach to identify a potential therapeutic target - Yang, Cao; Ge, Chang; Zhang, Wenjie; Xu, Jingxuan (Frontiers in Oncology, 2025)
BackgroundGlioma, particularly glioblastoma (GBM), remains a highly aggressive and challenging tumour, characterised by poor prognosis and limited therapeutic options. LSM2, an RNA-binding protein, has been implicated in tumour progression, yet its role in glioma remains underexplored. This study aims to investigate the expression, prognostic significance, and molecular mechanisms of LSM2 in glioma, focusing on its impact on RNA splicing regulation.MethodsClinical and transcriptomic data from 163 GBM and 518 lower-grade glioma (LGG) cases from The Cancer Genome Atlas (TCGA) were analysed to assess LSM2 expression and its prognostic value. RNA sequencing was performed on LSM2 knockdown in T98G glioblastoma cells to identify differentially expressed genes (DEGs) and alternative splicing events (ASEs). Bioinformatics tools were employed to perform functional enrichment analyses and construct protein–protein interaction (PPI) networks.ResultsLSM2 expression was significantly elevated in gliomas, particularly in GBM and in tumours with 1p/19q non-deletion or IDH1 mutation (p < 0.001). High LSM2 expression was correlated with shorter overall survival (HR = 1.7, p = 0.01). Knockdown of LSM2 in T98G cells identified 728 upregulated and 1,720 downregulated genes, alongside 1,949 splicing alterations, which primarily affected pathways related to RNA metabolism, DNA damage response, and cell cycle regulation. Key hub genes such as TLN1, FN1, and IRF7 were associated with glioma progression and poor prognosis.ConclusionOur findings demonstrate that LSM2 plays a critical role in glioma progression through the regulation of RNA splicing dynamics. Elevated LSM2 expression serves as a prognostic biomarker and offers promising potential as a therapeutic target in glioma.